Ionization of Helium by electron and proton impact. (August 2015) - Ambrosio, M J; Mitnik, D M; Gasaneo, G; Gaggioli, E L; Colavecchia, F D
Synopsis: We apply the Generalized Sturmian Functions method to the double ionization of Helium by fast electron and proton impact, obtaining fully differentiated cross sections which allow for a better understanding of the few-particle dynamics.